Sulfonamides: Historical Discovery Development (Structure-Activity Relationship Notes) - Farah Yousef; Oussama Mansour; Jehad Herbali (Journal of In-vitro In-vivo In-silico Journal, 2018)
Sulfonamide group is a magic group introduced as the main core for different bio-activities in drug industry. According to its substitutes, literature divides sulfonamide derivatives to antibacterial sulfonamides and non-anti-bacterial sulfonamides. As Data was collected from different sources such as Drug Bank.com and Pubchem.com databases and then was analyzed, we found that these compounds are different in their pharmacokinetics and pharmacodynamics; in addition to their sulfa cross allergy property. We presented these differences from these compounds changes in their chemical structure, in a way to build a solid base that can be depended on for developing new drugs from these compounds that interact with different receptors.
Keywords: sulfonamide derivatives